RESPON PERTUMBUHAN BEBERAPA VARIETAS TIMUN (Cucumi s sat i vus L. ) TERHADAP PEMBERIAN PUPUK ORGANIK - Vernando Simanullang; Mbue Kata Bangun; Hot Setiado (Universitas Sumatera Utara, 2014)
The research was conducted on the farm field with ± 25 meters above sea level from May to July2012. Randomized Block Design was used with 2 factors, ie: varieties (Hercules, Mercy and Harmony)and organic fertilizers (0, 100, 200, 300 g/plant). The parameters observed were plant height, the timeof flowering, the number of branches, the time of harvest, the fruit production per plant, the fruitlength, and the fruit diameter. The results showed that the varieties significantly affected: the plantheight 2, 3, and 4 week planted, the time of flowering, the number of branches, the time of harvest, thenumber of production per plant, the fruit length and the fruit diameter. Fertilizer significantly affectedto almost all of the observation parameters except the the plant heigh 2 week planted. The interactionbetween variety and organic fertilizer affected only to the fruit diameter.Key words: cucumber, variety, organic fertilizer